Variation in sustainability assurance practice: An analysis of accounting versus non-accounting providers. Issue 2 (March 2020) - Channuntapipat, Charika; Samsonova-Taddei, Anna; Turley, Stuart
Abstract: This study explores sustainability assurance (SA) practice as an arena of jurisdictional competition between accounting and non-accounting assurance providers. Prior literature on SA, a non-financial assurance practice, has documented the presence of both accounting and non-accounting firms as two major provider categories, pointing to the possibility of significant variation in practice among them. Unlike most prior studies that rely on the analysis of the content of SA reports, this article draws on an in-depth interview-based investigation of the practice. In particular, by reference to Abbott's theory of professions (1988), we explore efforts by different SA providers to claim their professional practice space. Our findings reveal notable differences in the providers' approaches to SA, both between and within the two key provider groups. We make sense of these differences as a consequence of the inter- and intra-professional competitive dynamics where different categories of providers appeal to and emphasize divergent knowledge bases and distinctive types of expertise as a way to differentiate themselves from competition and legitimize their practice approaches. This study contributes to the extant SA literature by providing a holistic overview of the practice field and an empirically drawn perspective on the nature of practice variation.